2022
DOI: 10.3389/fonc.2022.991948
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms by radiomic features on ultrasound imaging for predicting overall survival in patients with primary nodal diffuse large B-cell lymphoma

Abstract: ObjectivesTo develop and validate a nomogram to predict the overall survival (OS) of patients with primary nodal diffuse large B-cell lymphoma(N-DLBCL) based on radiomic features and clinical features.Materials and methodsA retrospective analysis was performed on 145 patients confirmed with N-DLBCL and they were randomly assigned to training set(n=78), internal validation set(n=33), external validation set(n=34). First, a clinical model (model 1) was established according to clinical features and ultrasound (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Patients with DLBCL differ in terms of their morphologic, immunophenotypic, clinical, and genetic features, and this heterogeneity underlies their different responses to chemotherapy regimens ( 2 ). Previously, the standard first-line treatment was cyclophosphamide, adriamycin, vincristine, and prednisone (CHOP), but more recent studies have shown that the addition of rituximab to CHOP (R-CHOP) decreases the risk of early and late recurrence ( 3 , 4 ). Subsequent clinical study reported that R-CHOP cures >50% of DLBCL patients, and this regimen is now accepted as a standard first-line treatment for DLBCL ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with DLBCL differ in terms of their morphologic, immunophenotypic, clinical, and genetic features, and this heterogeneity underlies their different responses to chemotherapy regimens ( 2 ). Previously, the standard first-line treatment was cyclophosphamide, adriamycin, vincristine, and prednisone (CHOP), but more recent studies have shown that the addition of rituximab to CHOP (R-CHOP) decreases the risk of early and late recurrence ( 3 , 4 ). Subsequent clinical study reported that R-CHOP cures >50% of DLBCL patients, and this regimen is now accepted as a standard first-line treatment for DLBCL ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative core needle biopsy (CNB) is an invasive examination and could not reflect the pathology of masses entirely for the heterogeneity of tumors. Otherwise, CNB may lead to complications such as severe bleeding and infection ( 12 ). Therefore, it is important to seek a non-invasive method to identify P-MC and FA and help clinicians make accurate clinical decisions ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%